Dinamika penegakan hak atas pendidikan: Tantangan dan realitas di Indonesia - nafiah, anna naylah (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the dynamics of Human Rights (HAM) enforcement in Indonesia’s education sector, which is constitutionally guaranteed through Article 31 of the 1945 Constitution and Law No. 39 of 1999. Despite the legal framework, field realities show significant access gaps, particularly for communities in 3T regions (Frontier, Outermost, Disadvantaged) and groups with disabilities due to infrastructure limitations and socio-economic factors. Beyond access barriers, this research highlights a surge in school violence reaching 614 cases by 2025, with educators as the dominant perpetrators at 57%. The impacts of these violations include physical and psychological trauma, as well as a decline in government credibility. The findings recommend massive human rights education, improved teacher distribution in remote areas through incentives, and the strengthening of inclusive and humanistic oversight mechanisms to realize a safe and dignified educational environment.